Violence in Popular U.S. Prime Time TV Dramas and the Cultivation of Fear: A Time Series Analysis - Daniel Romer; Patrick Jamieson (Media and Communication, 2014)
Gerbner and Gross’s cultivation theory predicts that prolonged exposure to TV violence creates fear of crime, symptomatic of a mean world syndrome. We tested the theory’s prediction in a time series model with annual changes in violence portrayal on popular US TV shows from 1972 to 2010 as a predictor of changes in public perceptions of local crime rates and fear of crime. We found that contrary to the prediction that TV violence would affect perceptions of crime rates, TV violence directly predicted fear of crime holding constant national crime rates and perceptions of crime rates. National crime rates predicted fear of crime but only as mediated by perceptions of local crime rates. The findings support an interpretation of cultivation theory that TV drama transports viewers into a fictive world that creates fear of crime but without changing perceptions of a mean world.